Is 3D just an addition of 1 to 2 or is it more enhancing than 2D visualizations? - Alam, G.M.; Oloruntegbe, O.K.; Oluwatelure, A.T.; Alake, E.M.; Ayeni, A.E. (Academic Journals, 2010)
There have been much reports of usefulness as well disadvantages of 3D environments in science teaching and learning when compared with 2D visualizations. The present study investigated the relative effectiveness of 2D and 3D visualizations on Nigerian Senior Secondary One students' understanding of molecular structure and nomenclature in organic chemistry. Quantitative data were generated using validated structured short answered questions. The instrument was administered before and after two intact groups of students (n = 60, 30 in each) were treated with 2D and 3D software supplemental following a conventional teaching. Treatment of the pre-test and post-test data using t-test statistic indicated no significant difference between the two groups even though the mean score of the 3D group was a little higher. In addition, the closeness of the mean scores which suggest that both 2D and 3D were good supplemental and the recommendation is that both should be used in teaching organic chemistry in schools. The excitement with which the students embraced 3D visualizations prove they might be more enhancing if students get used to the skills involved and the ability to fully comprehend them.